2011
DOI: 10.1007/s00330-011-2171-x
|View full text |Cite
|
Sign up to set email alerts
|

Making renal stones change size—impact of CT image post processing and reader variability

Abstract: Our results indicate a need for the standardisation of making measurements on CT images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…The 95% limits of agreement between our method and the mean reader value was 0.0±0.5 mm. This is comparable to the intrareader limit of agreement of ±0.5 mm and a narrower interval than the inter-reader limit of agreement of ±1.3 mm previously reported for the same data [5]. The use of a reader-independent segmentation algorithm is one way to reduce the inter-reader variability and thereby improve the information whereupon the treatment decision is based.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The 95% limits of agreement between our method and the mean reader value was 0.0±0.5 mm. This is comparable to the intrareader limit of agreement of ±0.5 mm and a narrower interval than the inter-reader limit of agreement of ±1.3 mm previously reported for the same data [5]. The use of a reader-independent segmentation algorithm is one way to reduce the inter-reader variability and thereby improve the information whereupon the treatment decision is based.…”
Section: Discussionsupporting
confidence: 75%
“…A previous study has demonstrated a larger interreader variability compared to the intra-reader variability [5].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Controversies Stone measurement on CT is not standardized and affects the reported size (whether to measure size in axial or coronal plane and whether to measure size on soft tissue or bone algorithm). 119 Ultrasound may approach CT for the initial diagnosis in the ED on clinical outcomes. 120 Pathophysiology Calcium oxalate (CaOx) and calcium phosphate are by far the most common stone composition.…”
Section: Pearlsmentioning
confidence: 99%